2018
DOI: 10.1038/s41598-018-20189-4
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genomes of Byrsonima species (Malpighiaceae): comparative analysis and screening of high divergence sequences

Abstract: Byrsonima is the third largest genus (about 200 species) in the Malpighiaceae family, and one of the most common in Brazilian savannas. However, there is no molecular phylogeny available for the genus and taxonomic uncertainties at the generic and family level still remain. Herein, we sequenced the complete chloroplast genome of B. coccolobifolia and B. crassifolia, the first ones described for Malpighiaceae, and performed comparative analyses with sequences previously published for other families in the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
117
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 63 publications
21
117
1
Order By: Relevance
“…In summary, the Ka/Ks values here provide comparative results for detection of selective pressure in mangrove chloroplasts. The genes that involve photosynthesis and energy metabolism for chloroplasts are conserved with very low Ka/Ks ratio, and this kind of evolutionary pattern has been generally observed in other plant chloroplasts [22,32]. The potential positive selection or relax pressure of ycf1 , rpl23 , rps7 , rpl36 , petL , psaI were also detected in mangroves, indicating their fast evolve rate and divergence in different species in spite of its ambiguous function in chloroplast genomes.…”
Section: Resultsmentioning
confidence: 78%
“…In summary, the Ka/Ks values here provide comparative results for detection of selective pressure in mangrove chloroplasts. The genes that involve photosynthesis and energy metabolism for chloroplasts are conserved with very low Ka/Ks ratio, and this kind of evolutionary pattern has been generally observed in other plant chloroplasts [22,32]. The potential positive selection or relax pressure of ycf1 , rpl23 , rps7 , rpl36 , petL , psaI were also detected in mangroves, indicating their fast evolve rate and divergence in different species in spite of its ambiguous function in chloroplast genomes.…”
Section: Resultsmentioning
confidence: 78%
“…The trn K intron is important because it expresses an unusual form of a group II intron derived from a mobile group of mitochondrial-like intron open reading frames (ORFs) (Hausner et al, 2006). As in the plastid genomes of many land plants, the abundance of A/T content at 3 rd base of codons was reported due to high concentration of A/T nucleotides in the whole plastid genome (Menezes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The plastomes of land plants have conserved structure but diversity prevails at the border position of LSC/SSC/IR of the genome. The size range of LSC, SSC and IR varies between the plastid genomes of species that advances to alterations in several genes and leads to the deletion of one copy of a gene or duplication of functional and non-functional genes of different sizes (Menezes et al, 2018; Saina et al, 2018). In the current study, all these ten Nicotiana species showed similarities with some variation as compared to the Nicotiana tabacum: in all these plants except Nicotiana tomentosiformis which have 60 bp in IRb region, the rps19 gene is present entirely in the LSC region but in Nicotiana tabacum rps19 gene extended 5bp in the IR region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations